2020
DOI: 10.1002/mp.14480
|View full text |Cite
|
Sign up to set email alerts
|

Correcting and reweighting false label masks in brain tumor segmentation

Abstract: Purpose Recently, brain tumor segmentation has made important progress. However, the quality of manual labels plays an important role in the performance, while in practice, it could vary greatly and in turn could substantially mislead the learning process and decrease the accuracy. We need to design a mechanism to combine label correction and sample reweighting to improve the effectiveness of brain tumor segmentation. Methods We propose a novel sample reweighting and label refinement method, and a novel three‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Therefore, using a DL algorithm to solve medical image segmentation has always been a research direction with theoretical significance and practical application value. Cheng et al proposed a sample reweighting and label refinement method and introduced a three-dimensional (3D) GAN to efficiently handle mislabel masks (21). Experiments on the BraTS19 dataset showed that this method obtained excellent results in handling the false labels in brain tumor segmentation.…”
Section: Medical Image Segmentationmentioning
confidence: 99%
“…Therefore, using a DL algorithm to solve medical image segmentation has always been a research direction with theoretical significance and practical application value. Cheng et al proposed a sample reweighting and label refinement method and introduced a three-dimensional (3D) GAN to efficiently handle mislabel masks (21). Experiments on the BraTS19 dataset showed that this method obtained excellent results in handling the false labels in brain tumor segmentation.…”
Section: Medical Image Segmentationmentioning
confidence: 99%
“…In addition, a residual module for conventional up- and downsampling has been added. The BraTS 2018 dataset was used to train this model, which resulted in a significant improvement in mIoU of 0.75 and a decrease in inference time [ 19 ].…”
Section: Background and Related Workmentioning
confidence: 99%
“…All images in the two datasets have been coregistered, interpolated, and skull-stripped. The training set is publicly accessible, but the groundtruth for validation set and test set is not open to access, BraTS 2015 1 and BraTS 2018 2 evaluation metrics are obtained by online evaluation.…”
Section: Datasetsmentioning
confidence: 99%
“…Gliomas are the most common brain tumors among the adults and one of the most deadly cancers. The clinical population with aggressive high‐grade gliomas (HGGs) usually has a life expectancy less than 2 years and requires immediate treatment 1 . As a nonintrusive imaging method, magnetic resonance imaging (MRI) is a powerful diagnostic approach for brain tumors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation